Upaya Peningkatan Motivasi Belajar Siswa Dengan Pendekatan Problem Based Learning Pada Pelajaran Kimia SMKN 1 Bukit Sundi Kecamatan Bukit Sundi Kabupaten Solok - Refriwati Refriwati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2015)
This research is aims to improve the competence of students in problem solving based in the learning students in problem solving based in the learning topic of electrolit liquid of grade XI TSM of SMKN 1 Bukit Sundi. It was a descriptive research to know and describe the competence of grade XI TSM of SMKN 1 Bukit Sundi. In learning thetopoc about electrolit liquid by using problem based learning approach. The data for this research were gathered from the test, presentation, assignmnet, students activit, students enthusiasm, and students partisipation in group, work discussion, and the students ability in presenting the result of discussion. The findings of this study are: [1].The score of the student activity that is relevant to the topic were increased compare from the circle one to circle two. [2].The score of the students activity is not relevant to the topic were decreased from circle one to circle two.